2020
DOI: 10.1192/bjp.2019.264
|View full text |Cite
|
Sign up to set email alerts
|

Typology of modifications to peer support work for adults with mental health problems: systematic review

Abstract: BackgroundPeer support work roles are being implemented internationally, and increasingly in lower-resource settings. However, there is no framework to inform what types of modifications are needed to address local contextual and cultural aspects.AimsTo conduct a systematic review identifying a typology of modifications to peer support work for adults with mental health problems.MethodWe systematically reviewed the peer support literature following PRISMA guidelines for systematic reviews (registered on PROSPE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 40 publications
4
22
0
Order By: Relevance
“…In addition, we would suggest that we have demonstrated that our approach to operationalising an analysis of organisational support for peer support is feasible and might be pursued in future reviews, subject to the availability of suitable data. Continued improvement in reporting peer support interventions might usefully include good description of the organisational support provided for peer workers [88].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we would suggest that we have demonstrated that our approach to operationalising an analysis of organisational support for peer support is feasible and might be pursued in future reviews, subject to the availability of suitable data. Continued improvement in reporting peer support interventions might usefully include good description of the organisational support provided for peer workers [88].…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of publication bias and heterogeneity in included papers are also limitations. Fifth, included publications were not analysed by diagnosis of PSW or target population, since peer support is a transdiagnostic intervention [43]. Finally, whilst strength of theme was used to order the identified influences, the magnitude and mechanisms of each influence were not investigated.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Vote-counting was used as a descriptive tool to indicate the strength of each theme. This has previously been used in other systematic reviews adopting a narrative synthesis (Charles et al, 2020). For stage 2, the relationships within and between studies were explored.…”
Section: Discussionmentioning
confidence: 99%